Caminhos e singularidades dos papéis ocupacionais na parentalidade adotiva: uma perspectiva sobre a literatura recente - Rosilho, Alice da Silva (Universidade Federal de São Carlos, 2025)
The construction of occupational roles is an essential element in occupational therapy, as it reflects how individuals engage in meaningful activities in their daily lives. In the context of adoptive parenting, sociocultural values still influence how this role is perceived, often devaluing adoption in comparison to biological parenthood. Based on the Model of Human Occupation (MOHO), occupational therapy must recognize that parenting goes beyond biological markers, encompassing social, symbolic, and subjective aspects. Regarding motherhood, social transformations have chosen to become a mother more evident, yet challenges remain in equating adoptive and biological parenting. Similarly, the father’s role is often reduced to playful and financial aspects, reinforcing inequalities in caregiving responsibilities. Given this, occupational therapists play a fundamental role in redefining adoptive parenting, promoting interventions that value this process and supporting families in building emotional bonds. The profession can contribute to deconstructing normative standards and strengthening the recognition of adoption as a legitimate and fulfilling experience of parenthood.
Paths and singularities of occupational roles in adoptive parenting: a perspective on recent literature
Keywords: Parentalidade; Adoção; Terapia ocupacional; Parenting; Adoption; Occupational therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL